The correct name of Radermachera pinnata (Bignoniaceae) - Turner, I. M. (Phytotaxa, 2012)
The names of two widespread tree species from tropical Asia, Radermachera pinnata (Blanco) Seemann (1870: 147) (Bignoniaceae) and Meliosma pinnata (Roxb.) Maximowicz (1867: 64) (Sabiaceae), are based on the orthographically identical binomial Millingtonia pinnata. The earlier of the two basionyms is Millingtonia pinnata Roxburgh (1820: 103), making Millingtonia pinnata Blanco (1837: 501) an illegitimate later homonym. Radermachera pinnata must therefore be considered an avowed substitute with priority dating from 1870 (ICBN Art. 58.1; McNeill et al. 2006). However, there are several names with priority over Radermachera pinnata (see synonymy in van Steenis 1976). The earliest of these is Millingtonia quadripinnata Blanco (1837: 501). Merrill (1908) was the first to equate Blanco’s two species of Millingtonia, and he reduced M. quadripinnata to a synonym of M. pinnata. Merrill’s interpretation of the identity of M. quadripinnata was followed by van Steenis (1928, 1976, 1977), but the application of the name remains unfixed in the absence of a type. There are no extant Blanco specimens (Veldkamp 1989, Nicolson & Veldkamp 2003), so neotypification is required. This is done here to secure the accepted application of the name. The correct name for Radermachera pinnata therefore becomes R. quadripinnata. A new combination is required for a widely recognised subspecies. This is made below.